DYNAMICS OF LURING LEARNING IN THE PANDEMIC TIME COVID-19 IN MTS "EL-JASMEEN" SINGOSARI DISTRICT, MALANG - Medida, Veneshia Auralia; Purnomo, Agus (Proceeding of International Conference on Islamic Education (ICIED); Vol 5 No 1 (2020): Proceeding of International Conference on Islamic Education (ICIED), 2021)
This article aims to obtain information regarding the impact of the Covid-19 pandemic, which affects the implementation process of learning at junior high schools, especially at MTs El-Jasmeen. This research uses a case study method with topics such as the learning process carried out at MTs El-Jasmeen during the Covid-19 pandemic, prevention of covid-19 transmission in each student, and students' interest in learning in the classroom. The Covid-19 pandemic has impacted many things, including in education, shaken teaching, and learning activities. The learning activities at MTs El-Jasmeen still uses offline learning, which has been coordinated with the parents and the local school principal by following government directions and recommended health protocols. In this case,